Gambaran Intensitas Nyeri, Dampak Aktivitas Belajar, dan Koping Remaja yang Mengalami Dismenore - Bethari Karlinda; Oswati Hasanah; Erwin (Jurnal Vokasi Keperawatan (JVK), 2022)
The level of complaints of dysmenorrhea depends on the intensity of the pain felt. Dysmenorrhea can affect daily activities, especially for teenagers, and it will have an impact on their learning activities. Therefore coping is needed to adapt to the changes received due to dysmenorrhea. This study aims to describe the intensity of pain, the impact of learning activities, and the coping of adolescents with dysmenorrhea. This research was conducted at the Faculty of Nursing, the University of Riau using a descriptive method. The sample in this study was 159 respondents with a stratified random sampling technique. The results showed that the majority of respondents were at the age of 19 years (51.6%), the most menarche was at the age of 12 years (40.3%), and most of the respondents experienced dysmenorrhea with moderate pain intensity (71.7%), the majority of respondents experienced the impact of disrupted learning activities (58.5%), and most of the coping done by adolescents were adaptive coping (67.9%). The results of this study are expected to be a source of information for nursing science and research institutions so that they can take appropriate treatment so that dysmenorrhea does not interfere with learning activities and can examine the effect of coping mechanisms on the learning activities of adolescents who experience dysmenorrhea for future researchers.